Comparison of cobas 4800, m2000, Viper XTR, and Infinity 80 Automated Instruments When Processing Urine Specimens for the Diagnosis of Chlamydia trachomatis and Neisseria gonorrhoeae. Issue 2 (March 2017) - Chernesky, Max A.; Jang, Dan; Gilchrist, Jodi; Smieja, Marek; Arias, Manuel; Hatchette, Todd; Poirier, Andre; Mayne, Donna; Ratnam, Sam
Abstract : Objectives: North American and European advisory groups recommend testing for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) with nucleic acid amplification tests. Testing is often performed on automated instruments. The objectives of this study were to process urines for the diagnosis of CT and NG and to examine workflow procedures and outcomes. Methods: While processing 1, 24, 48, 96, and 192 urine specimens on 3 batch-mode systems which use 96-well plates: cobas 4800, m 2000, and Viper XTR and the random access cartridge testing GeneXpert Infinity 80, we measured assay performance, hands-on time for processing and maintenance, reagents and plastics consumption, time required to obtain results, and testing accuracy. Results: The Infinity 80 required the least hands-on time for single specimens and smaller batches, whereas the Viper XTR and m 2000 required the most hands-on time for all batch sizes. Cumulative daily, weekly, and monthly maintenance was highest for the Viper XTR and lowest for Infinity 80. All batch-mode instruments consumed large amounts of disposables. Time to results was shortest for the Infinity 80, and the Viper XTR provided the shortest time for the batch-mode instruments. All systems showed similar diagnostic accuracy. Conclusions: Because detection performances were similar, issues of hands-on time, maintenance, time to results, and consumables are important operational factors for the diagnosis and treatment of CT/NG infections. Abstract : Random access and batch-mode systems for diagnosing Chlamydia trachomatis and Neisseria gonorrhoeae infections show differences in performance parameters, such as time to results, hands on time, and maintenance.